Lesbian, Gay, Bisexual, and Transgender (LGBT) in Muslim Society - Isnaini, Nurlaila; Maseleno, Andino (STAI Publisistik Thawalib Jakarta, 2024)
TThe LGBT phenomenon triggers both support and opposition, especially in Muslim-majority countries. Some nations legalize same-sex marriage. In Indonesia, rejection of LGBT arises through regulations and psychological efforts. This study aims to explore LGBT Muslims in Muslim communities more deeply. This research is a literature review, where all data sources are analyzed thoroughly. The results of the study reveal various perceptions within society regarding LGBT behavior. Reasons provided by different parties, including LGBT activists and individuals, contribute to the growing debate. Some oppose LGBT behavior, arguing it contradicts religious, cultural, and societal norms, while others support it as a form of freedom to express one’s rights. Conclusion: The LGBT issue sparks both support and opposition, especially in Muslim-majority countries, with rejection in Indonesia through regulations and psychological efforts.